Future skills and workforce evolution – training and skills development for mining operation engineer and drill and blast engineer in surface mineral mine PT Indo Muro Kencan - H Utama; R Heryadi (The Australasian Institute of Mining and Metallurgy, 2024)
PT Indo Muro Kencana (PT IMK) is a surface gold and silver mine located in Mt. Muro area, Central Kalimantan province, Indonesia. The mining operations of multiple open pits using combination of excavator and haul truck is operated. This operation is performed in two shifts in a day. The articulated dump truck (ADT) with capacity of 40 t and 60 t deliver ore to the mineral processing plant and discard waste material to the waste dump area. Overall, PT IMK’s mining operation department is consisting of two sections, namely mining operation section and drill and blast section. Firstly, mine operation section is responsible to manage loading, hauling, pit service (mine dewatering, earthwork, road maintenance) and mine operation engineering. Secondly, drill and blast section is in charge to manage drilling and blasting (blast engineering, blasting operation, explosive permit and magazine or explosive storage). Additionally, conventional blasting method (ore-waste blasting) with non-electric initiation system is used and sleep blasting is undertaken as bulk explosive is buried for maximum two days. The first purpose of this paper is to elucidate about role of mining engineer in mining operation department (mining operation engineer and D&B engineer). At this point, mining operation engineering practice (fleet management system, production control and mining manpower management) and also blasting daily practice will be elucidated. Daily blasting practice is consisting of surface blast design, explosive engineering, sleep blast practice and the concept of scaled depth of burial to ensure a safe work environment in blasting activity. Next, the second purpose of this paper is to explore workforce evolution and future skills for mining engineer in surface mining operation. Furthermore, strategy to advance future skills such as mining continuous improvement program, training and skills development for mining engineer (mining operation engineer and D&B engineer) in order to develop their skills is also discussed. It is expected that in the future, these future mining leaders will become new mining leader, for instance mining superintendents, D&B superintendents and mining managers. In conclusion, it is clear that awareness about workforce evolution, professional development, training, skills development, mining economics awareness and mining continuous improvement program are essentially required as professional development for mining engineer (mining operation engineer and D&B engineer), in order to be commercially competitive in their future career and in order to be adapted with future workforce evolution in mining.